RELIGIOUS TOLERANCE AS A DA'WAH MOVEMENT PLURALIST SOCIETY IN INDONESIA - Madnasir Madnasir; Mohammad Fikri Nugraha Kholid (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
Indonesian Muslims are faced with the emergence of a small number of intolerant, exclusive, rigid Islamic groups and other groups that easily express hostility and carry out conflicts. On the other hand, Muslims are also faced with the emergence of an Islamic community that tends to be liberal and permissive. The two groups are classified as the extreme right (tatorruf yamini) and the extreme left (tatorruf yasari), which are against the ideal form of implementing Islamic teachings in Indonesia and even the world. In fact, Islam has very clearly taught about tolerance in religion, especially since Indonesia is a pluralist country that adheres to many religions. This study uses qualitative method. While the data collection is using literature study information. This research obtained several important findings that da'wah is an obligation that every Muslim should carry and convey in wise and wise ways. In the implementation of da'wah in a pluralist society, the method of da'wah bi al-hikmah must be put forward. The diversity or plurality of human life in various ways is sunnatullah. Living in a pluralistic society will exist if everyone understands each other, respects each other, and accepts each other.